The Relationship Between Minimum Wage and Education Index with Unemployment in the Regencies and Cities of East Java - Affandi, Hafis Demas; Syafitri, Wildan; Bintoro, Nugroho Suryo (Journal of International Conference Proceedings, 2023)
Unemployment is an interesting topic to discuss because it is an endless issue, and several factors influencing unemployment can be very complex. Unemployment is a problem that is always present and never-ending for debate. This study aims to examine the effect of Minimum Wage and Education Index on Unemployment in the Regencies and Cities of East Java during the research period of 2010-2022. The data used in this study are secondary data of a panel type, consisting of 13 years of time series data from 2010 to 2022, and cross-sectional data of 38 Regencies/Cities in East Java sourced from the Central Bureau of Statistics (BPS). The data is quantitative and processed using multiple linear regression analysis. The study found that the minimum wage (X1) variable has a significant positive impact on unemployment, the education index (X2) variable has a significant positive impact on unemployment (Y), and both the minimum wage (X1) and education index (X2) variables together have an impact on unemployment (Y) in the Regencies and Cities of East Java.